2016
DOI: 10.1617/s11527-016-0951-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the vibration alleviation of a new railway sub-ballast layer with waste tyre rubber

Abstract: This paper focuses on the assessment of the vibration behaviour of granular subballast materials mixed with rubber particles from scrap tyres. The main objective is to evaluate whether these mixes attenuate vibrations caused by passing trains, and if so, to what extent. Several laboratory and field tests were carried out to monitor the response of such materials to various excitation sources. The results show that under controlled laboratory conditions, the addition of rubber (up to 5% by weight) greatly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Senetakis et al [38] reported that the maximum damping ratio of pure sand is less than 10%, whereas the corresponding value is up to 15% for sand-tire shred mixtures. Because of its high energy dissipation capacity, this mixture has been used in other engineering applications such as railway sub-ballast layers [39,40] and geotechnical seismic isolation [41][42][43]. Xiong and Li [44] showed that geotechnical seismic isolation could effectively mitigate seismic hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Senetakis et al [38] reported that the maximum damping ratio of pure sand is less than 10%, whereas the corresponding value is up to 15% for sand-tire shred mixtures. Because of its high energy dissipation capacity, this mixture has been used in other engineering applications such as railway sub-ballast layers [39,40] and geotechnical seismic isolation [41][42][43]. Xiong and Li [44] showed that geotechnical seismic isolation could effectively mitigate seismic hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Towards these limitations, the reuse of waste rubber in ballast bed is proposed as a solution, but few studies on this have been performed. This topic is necessary and worthwhile to study because it can reduce the ballast degradation [10,11], absorb noises [12][13][14] and dispose waste rubber (low costs). However, due to the limited numbers of research, the studies did not always reach the same conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the optimal percentage, another research gap is the effects of the CR size on the ballast degradation reduction. Some of earlier studies utilised the same Particle Size Distribution (PSD) as the ballast [11,15], while most of the other studies utilised smaller rubber sizes under 20 mm [10,12,16]. Even though the studies proved the addition of the CR can reduce ballast degradation and absorb the vibration, the results can be more reliable and useful when the rubber size is confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…In the automotive applications, the annual demand for rubber shock absorber has reached several hundred millions, and the number is attempt to rise year by year. With the development of railway, the demand for rubber shock absorber is becoming larger and larger [3,4] . Moreover, the bridge bearing is also widely used rubber shock absorber [5] .…”
Section: Introductionmentioning
confidence: 99%